Illocutionary Speech Acts in the Lyrics of “Mathasibnish” Based on Searle’s Theory - Ashfa Sabila Zahro'; Ahmad Kholil (Hasanuddin University, 2026)
Song lyrics as a form of poetic text not only serve an aesthetic function but also contain a communicative dimension that reflects the speaker’s attitudes, intentions, and emotional states within interpersonal relationships. In the context of modern popular Arabic music, themes of betrayal and disappointment are frequently represented through language rich in pragmatic meaning. This study aims to examine the realization of illocutionary speech acts in the lyrics of “Mathasibnish” written by Amir Teima and popularized by Sherine Abdel Wahab. The research employs a qualitative descriptive approach, drawing on speech act theory proposed by J. L. Austin and further developed by John Searle, which classifies illocutionary acts into representative, directive, commissive, expressive, and declarative categories. The data consist of utterances in the song lyrics, collected through documentation techniques and analyzed through processes of identification, classification, and interpretation of their pragmatic functions. The findings reveal that four types of illocutionary speech acts are present in the lyrics, namely representatives, directives, commissives, and expressives, while declaratives are not identified. The dominance of expressive acts emphasizes that the song discourse is oriented toward the expression of emotion, particularly feelings of disappointment and inner pain resulting from betrayal. Meanwhile, representative, directive, and commissive acts function to reinforce the speaker’s position and decisions within the relationship.